Structural characterisation, anticandidal activity and mode of action of a tryptophan end-tagged tick-derived peptide - Gaspar, A.R.M. (Anabella Regina Marques) (University of Pretoria, 2024)
Thesis (PhD (Biochemistry))--University of Pretoria, 2024.